Influence of Bone Anisotropy on Stress Distribution and Optimum Shape of Cementless Femoral Implants - Kowalczyk, P. (Engineering Transactions, 2003)
Implant separation from bone tissue, resulting in the necessity for revision surgery, is a serious drawback of cement less total joint replacement. Unnatural stress distribution around the implant is considered the main reason for the failure. Optimization of the implant properties, especially its geometric parameters, is believed to be the right way to improve reliability of joint prosthetics. Numerical models of femur-implant system enabling approximate analysis of stress distribution and shape optimization of implants suffer from numerous simplifications as, e.g., the assumption of bone isotropy, which may put in question reliability of the results obtained. In this paper, a numerical model including orthotropic properties of both cancellous and cortical bone is presented and influence of this assumption on results of the analysis and optimization is investigated.